2021
DOI: 10.1159/000514248
|View full text |Cite
|
Sign up to set email alerts
|

A 3D-Printed Model-Assisted Cervical Spine Instrumentation after Tumor Resection in a 4-Year-Old Child: A Case Report

Abstract: <b><i>Introduction:</i></b> In the case of tumor resection in the upper cervical spine, a multilevel laminectomy with instrumented fixation is required to prevent kyphotic deformity and myelopathy. Nevertheless, instrumentation of the cervical spine in children under the age of 8 years is challenging due to anatomical considerations and unavailability of specific instrumentation. <b><i>Case Presentation:</i></b> We present a case of 3D-printed model-assisted cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Another similar operator was applied to generate SVM clustering, like a Kayyali Operator, which was working based on a perfect convolution filter 3x3 [3]. For the detection of brain tumour, SVM clustering is at the forefront of computer vision systems and it needs quality inspection and evaluation [12] [13]. Contour coding technique provides a relatively simple but precise methodology for edge detection problems, with more demanding requirements on the accuracy and robustness of the detection, the traditional algorithm can no longer handle the challenging task of edge detection.…”
Section: Discussionmentioning
confidence: 99%
“…Another similar operator was applied to generate SVM clustering, like a Kayyali Operator, which was working based on a perfect convolution filter 3x3 [3]. For the detection of brain tumour, SVM clustering is at the forefront of computer vision systems and it needs quality inspection and evaluation [12] [13]. Contour coding technique provides a relatively simple but precise methodology for edge detection problems, with more demanding requirements on the accuracy and robustness of the detection, the traditional algorithm can no longer handle the challenging task of edge detection.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no significant differences in morbidity, length of hospital stay, postoperative imaging results, or pedicle screw deviation compared with conventional groups' personalized implants. Jug M. et al [37] showed a case of a 3D printed model to assist cervical spine instruments, using 3D virtual planning to evaluate and plan retrocervical spine fixation surgical plans, using 3D printed models to confirm the feasibility of fixation "in vitro" before surgery, and minimizing the possibility of intraoperative implant-spine mismatch. The outcome was that the intraoperative conditions were exactly similar to the preoperative plan and the screws were successfully inserted as planned.…”
Section: Preoperative Planning and Surgical Simulationmentioning
confidence: 99%